Religion in China: Survival and Revival under Communist Rule - Yang, Fenggang (Oxford University Press USA - OSO, 2011)
In Religion in China, Fenggang Yang provides a comprehensive overview of the religious change in China under Communism, drawing on his ''political economy'' approach to the sociology of religion.